Moderate Exercise in Spontaneously Hypertensive Rats Is Unable to Activate the Expression of Genes Linked to Mitochondrial Dynamics and Biogenesis in Cardiomyocytes - Quiroga, Clara; Mancilla, Georthan; Oyarzun, Ingrid; Tapia, Anita; Caballero, Mia; Gabrielli, Luigi A.; Valladares-Ide, Denisse; del Campo, Andrea; Castro, Pablo F.; Verdejo, Hugo E. (Frontiers in Endocrinology, 2020)
Hypertension (HTN) is a public health concern and a major preventable cause of cardiovascular disease (CVD). When uncontrolled, HTN may lead to adverse cardiac remodeling, left ventricular hypertrophy, and ultimately, heart failure. Regular aerobic exercise training exhibits blood pressure protective effects, improves myocardial function, and may reverse pathologic cardiac hypertrophy. These beneficial effects depend at least partially on improved mitochondrial function, decreased oxidative stress, endothelial dysfunction, and apoptotic cell death, which supports the general recommendation of moderate exercise in CVD patients. However, most of these mechanisms have been described on healthy individuals; the effect of moderate exercise on HTN subjects at a cellular level remain largely unknown. We hypothesized that hypertension in adult spontaneously hypertensive rats (SHRs) reduces the mitochondrial response to moderate exercise in the myocardium. Methods: Eight-month-old SHRs and their normotensive control—Wistar-Kyoto rats (WKYR)—were randomly assigned to moderate exercise on a treadmill five times per week with a running speed set at 10 m/min and 15° inclination. The duration of each session was 45 min with a relative intensity of 70–85% of the maximum O2 consumption for a total of 8 weeks. A control group of untrained animals was maintained in their cages with short sessions of 10 min at 10 m/min two times per week to maintain them accustomed to the treadmill. After completing the exercise protocol, we assessed maximum exercise capacity and echocardiographic parameters. Animals were euthanized, and heart and muscle tissue were harvested for protein determinations and gene expression analysis. Measurements were compared using a nonparametric ANOVA (Kruskal-Wallis), with post-hoc Dunn's test. Results: At baseline, SHR presented myocardial remodeling evidenced by left ventricular hypertrophy (interventricular septum 2.08 ± 0.07 vs. 1.62 ± 0.08 mm, p < 0.001), enlarged left atria (0.62 ± 0.1 mm vs. 0.52 ± 0.1, p = 0.04), and impaired diastolic function (E/A ratio 2.43 ± 0.1 vs. 1.56 ± 0.2) when compared to WKYR. Moderate exercise did not induce changes in ventricular remodeling but improved diastolic filling pattern (E/A ratio 2.43 ± 0.1 in untrained SHR vs. 1.89 ± 0.16 trained SHR, p < 0.01). Histological analysis revealed increased myocyte transversal section area, increased Myh7 (myosin heavy chain 7) expression, and collagen fiber accumulation in SHR-control hearts. While the exercise protocol did not modify cardiac size, there was a significant reduction of cardiomyocyte size in the SHR-exercise group. Conversely, titin expression increased only WYK-exercise animals but remained unchanged in the SHR-exercise group. Mitochondrial response to exercise also diverged between SHR and WYKR: while moderate exercise showed an apparent increase in mRNA levels of Ppargc1α, Opa1, Mfn2, Mff, and Drp1 in WYKR, mitochondrial dynamics proteins remained unchanged in response to exercise in SHR. This finding was further confirmed by decreased levels of MFN2 and OPA1 in SHR at baseline and increased OPA1 processing in response to exercise in heart. In summary, aerobic exercise improves diastolic parameters in SHR but fails to activate the cardiomyocyte mitochondrial adaptive response observed in healthy individuals. This finding may explain the discrepancies on the effect of exercise in clinical settings and evidence of the need to further refine our understanding of the molecular response to physical activity in HTN subjects.